An Improved Version of ETS-Regression Models in Calculating the Fixed Offshore Platform Responses - Sayyid Zainal Abidin Syed Ahmad; Mohd Khairi Abu Husain; Noor Irza Mohd Zaki; Nurul ‘Azizah Mukhlas; Gholamhossein Najafian (Journal of Marine Science and Engineering, 2022)
An offshore structural design should accurately calculate wave loads and structural responses acting on slender cylinders. The hydrodynamic drag-dominated force was always challenging, hence the hydrodynamic wave loading became a complex solution; it led to a nonlinear relation between the wave force and responses caused by the diffracted and radiated waves, which was included in Morison’s equation. For more consistency in the structural assessment, the linearised drag–inertia force was considered in model development, such as an improved version of the efficient time simulation regression (ETS-Reg) procedure that was introduced. The study aimed to improve the prediction of structural responses using the predetermined linear, polynomial, and cubic regression models. These simulations were performed focusing on high sea state conditions without wave-induced current effects. In order to evaluate the level of accuracy, the recent ETS-Reg models were compared and validated using the Monte Carlo time simulation (MCTS) method. An amended ETS-Reg model, known as the ETS-RegLR model, was also compared with the previous results obtained using the conventional ETS-Reg models (ETS-RegSE), leading to better structural response calculations.